Correlation Between Type 2 Diabetes Mellitus and Pulmonary Tuberculosis at Atma Jaya Hospital - Mario Steffanus; Anastasia Pratiwi Fodianto; Jessica Novia Hadiyanto (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2021)
Background: Diabetes Mellitus (DM) is considered one of the factors that increase the risk of pulmonary tuberculosis (TB). Tuberculosis in Indonesia is severe and ranked second in the world after India. Previous studies suggested that DM increased the risk of developing pulmonary TB by 2–5 times. This study was conducted to determine the effect of type 2 DM on the incidence of pulmonary TB at Atma Jaya Hospital. Methods: This was a case-control study conducted at Atma Jaya Hospital from December 2016 to April 2017 using medical records. Data were further processed by pairing gender and age between case and control groups. A total of 121 samples were obtained and tested using McNemar paired correlation non-parametric analysis. Results: The incidence of pulmonary TB was higher in men than women with a ratio of 2.1:1 and within the productive age range of 27–46 years. The percentage of type 2 DM in pulmonary TB cases was 70% (35 samples) compared to 30% (15 samples) without DM with a total of 50 samples in the case group. The percentage of type 2 DM in the control group without pulmonary TB was 46.5% (33 samples) compared to 53.5% (38 samples) without DM with a total of 71 samples in the control group. Based on the statistical analysis, the P=0.013 and the OR (odds ratio) was 2.20. Conclusion: There was a significant correlation between type 2 DM and the incidence of pulmonary TB in Atma Jaya Hospital with the risk of pulmonary TB 2.20 times higher than those without type 2 DM.